Creating Fluorine‐Doped MoS2 Edge Electrodes with Enhanced Hydrogen Evolution Activity. Issue 11 (12th September 2021) - Zhang, Ruihua; Zhang, Mengru; Yang, Hao; Li, Gen; Xing, Shuming; Li, Mengyan; Xu, Yiling; Zhang, Qiuyue; Hu, Sheng; Liao, Honggang; Cao, Yang
Abstract: The edge sites of MoS2 are catalytically active for hydrogen evolution reactions (HER). However, pristine edge sites usually contain only intrinsic atoms or defects, limiting the tuning of on‐site hydrogen species adsorption and desorption, the critical steps for HER. In addition, the number of atoms on pristine edges is small compared to that of electrochemically inert atoms in bulk. Thus, it is desirable to develop a scalable technique of creating a large number of highly HER‐active edge sites. Here, a plasma etching strategy is developed for creating MoS2 edge electrodes with a controllable number of active sites that enable the quantitative characterization of their HER activity using a local probe method. Fluorine atoms with large electronegativity are doped on the MoS2 edge sites that lead to a fivefold activity enhancement compared to that from pristine edges and is attributed to the more moderate binding energy for hydrogen species. The scalability of such a method is further demonstrated by activating MoS2 catalyst in macroscopic quantities with enhanced HER performance and stability. The work provides two‐dimensional materials as a platform for understanding the doping effect on the edge sites at atomic‐level, and offers a novel route for the design of efficient catalysts. Abstract : A scalable plasma etching strategy is developed for creating abundant fluorine‐doped edge sites on MoS2 nanosheets. Quantitative measurement of each single edge site based on electrocatalytic microdevices has been carried out. The results suggest this method can not only increase a large density of active edge sites, but also enhance their intrinsic hydrogen evolution reaction (HER) activity simultaneously.